If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -81 = -12 Reorder the terms: -81 + y = -12 Solving -81 + y = -12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + y = -12 + 81 Combine like terms: -81 + 81 = 0 0 + y = -12 + 81 y = -12 + 81 Combine like terms: -12 + 81 = 69 y = 69 Simplifying y = 69
| -8y+12=-28 | | 61+x=5 | | 9+8x=72+8 | | 3x-2x=-3-2x | | 19=4n+7 | | 5x+3-4x=9 | | 73-6x=30x+17 | | X-.28x=463.32 | | 2-4y=1-5y | | 3x+(2x+4)=5(x+1)+3 | | 5x+6=-69 | | -4[x-2(2x-3)]+1=x-3 | | x-(-50)=55 | | -10-8p+15+9p=2 | | 11x^2-8=432 | | 6+0.60x=13.20 | | -9+3b=12 | | 8-5q=21-2q | | 6X(2x-5)=0 | | x-(-54)=-11 | | 2y^2+10y-48= | | 9x+9+4x=39 | | Y=x^2+9x+19 | | x-62=-20 | | 7-5x=x-12 | | 2x^2-48x=0 | | (-1)x=-(-10) | | 4(6y-12)-2y=-4 | | -x+92=2x-3x | | x^2-4s+4=0 | | 16+x=-73 | | X+17-3X=11 |